The Effect of Funnel Counting Learning Media On Mathematical Logic Intelligence Second Grade Elementary School Students - Linda Astriani; Rifdah Hasna Jauza (Universitas Pendidikan Indonesia (UPI), 2024)
This research is based on the low ability of students Overcome difficulties and find optimal answers. multiplication material, which is caused by the lack of use of learning media in schools. This study aims to determine the effect of using funnel counting learning media on the mathematical logic intelligence of grade II elementary school students. Therefore, the study was carried out using quantitative techniques. using quasi experimental research type and posttest only control design. This research was conducted at SDN Rempoa 01 in the school year 2023/2024 even semester. The study population consisted of class II students totaling 116 people. The research sample consisted of 30 students as the control class and 31 students as the experimental class, which were selected using purposive sampling technique. The instruments used in this study include test and non-test instruments. The test instrument is a post-test with 13 description questions to measure mathematical logic intelligence, while the non-test instrument is in the form of student documentation. The data analysis of this study was assisted by the SPSS V.26 application. The results of the Independent Sample T-test test showed a significance value of 0.0001 0.05 and a tcount value of 18.459 table of 2.001, so Ho was rejected and Ha was accepted. This shows that there is an effect of learning media funnel counting on the mathematical logic intelligence of grade II students of SDN Rempoa 01 South Tangerang.